Sistem Pemantauan Detak Jantung dan Suhu Tubuh menggunakan Protokol Komunikasi MQTT - Fathul Hakim; Heru Nurwarsito (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The large number of patients who do not have money so that they have to be treated outpatient causes new problems. The number of diseases caused by heart organs and human body temperature is an important problem. Based on the cases that have occurred, we need a system to monitor heart rate and body temperature. To solve this problem the design of the heart rate and body temperature was carried out using MQTT (Message Queuing Telemetry Transport) delivery. Heart rate reading uses a pulse oxymeter sensor by attaching the thumb to the sensor and the body temperature sensor LM35 by handheld. Data processing is done by using Wemos D1 and online storage namely cloud by utilizing the mqtt communication protocol. The process of displaying data is done in realtime. The test results on the two sensors give different results, namely 6.1 for heart rate sensors and 0.9 for body temperature sensors. Whereas for RTT (Round Trip Time) testing the system can complete less than 1 minute.